Mapping versatile boundaries : understanding the Balkans - Darques, Regis (Springer, 2016)
This book demonstrates the pivotal role played by state confines in the geography of Balkan countries through powerful GIS and remote sensing analyses. It provides unique mapping perspectives on the Balkan region, with over 140 illustrations. The book is dedicated to applied, historical and economic geographers, as well as political scientists. Because of its high fragmentation, the Balkan area has not been studied on a systematic transnational basis. The persistence of frozen and/or open conflicts has also turned the border issue into an absolute taboo subject for the scientific community and civil society. This results in an apparent "chaos" that most Western observers fail to understand.- Resumé vydavatel
Keywords: geopolitika -- Balkánský poloostrov; státní hranice -- Balkánský poloostrov; geografické informační systémy; geografie -- Balkánský poloostrov; geopolitics -- Balkan Peninsula; boundaries -- Balkan Peninsula; geographical information systems; geography -- Balkan Peninsula; Balkánský poloostrov -- dějiny; Balkan Peninsula -- history; elektronické knihy; monografie; electronic books; monographs